Pengaruh Pendapatan Murabahah dan Pendapatan Musyarakah Terhadap Profitabilitas Pada PT. Bank BNI Syariah - Supriyanto, Dodi; Kusuma, Daeng (2017)
This study aims to determine how the development of murabahah income and musharaka income and its effect on profitability (ROA). Factors tested in this study are murabahah and musyarakah income as independent variables and profitability is the dependent variable. The subject of this study is Bank BNI Syariah. The research method used in this study is descriptive and verification methods. The population used is secondary data on the financial statements of Bank BNI Syariah for the 2012-2016 period. And the sample is murabahah income, musharaka income and profitability (ROA). This method of analysis is multiple linear regression. At a significance level of 5%. The program used in analyzing data uses statistical package for social science (SPSS) versus 25. The results showed that partially obtained murabahah income value of 1.062 with a significance of 0.303 which means that murabahah income (X1) has a positive and influential relationship, but not significant to profitability. Whereas musyarakah income obtained a value of -0.081 with a significant level of 0.936, which means that musharaka income has a negative but not significant effect on profitability. While murabahah and musyarakah income simultaneously but not significant to profitability (ROA) simultaneously.